2015
DOI: 10.1186/s12906-016-1030-3
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of Xue-Fu-Zhu-Yu decoction, Tian-Ma-Gou-Teng-Yin and Wen-Dan decoction on myocardial fibrosis in a hypertensive rat mode

Abstract: BackgroundXue-Fu-Zhu-Yu decoction (XFZYD), Tian-Ma-Gou-Teng-Yin (TMGTY) and Wen-Dan decoction (WDD) are Chinese herbal formulas used to treat hypertension and cardiovascular diseases in traditional Chinese medicine (TCM). The goal of our study is to determine if XFZYD, TMGTY or WDD treatment ameliorated myocardial fibrosis in spontaneously hypertensive rats (SHRs) and to identify the mechanisms underlying any beneficial effects observed during the courses of the investigation.MethodsForty-five 12-week-old male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Results of previous studies have shown that TMGTY has significant effects on a variety of HTN-caused cardiovascular diseases [14]. Recent scientific evidence has also demonstrated that TMGTY provides neuroprotective effects for patients with Parkinson’s disease [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of previous studies have shown that TMGTY has significant effects on a variety of HTN-caused cardiovascular diseases [14]. Recent scientific evidence has also demonstrated that TMGTY provides neuroprotective effects for patients with Parkinson’s disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that HTN has been consistently associated with an increased risk of dementia in most cross-sectional and longitudinal cohort studies, and appears to be more relevant when it presents in middle age rather than later in life [10–12]. Results of previous studies have demonstrated that TCM can lower blood pressure and modify vascular risk factors in patients with HTN [13, 14], which may be related to dementia [15, 16]. However, to our knowledge, there is a paucity of information on the benefit of TCM for dementia risk, in particular for subjects with HTN.…”
Section: Introductionmentioning
confidence: 99%
“…Tian-Ma-Gou-Teng-Yin was prescribed for neurodegenerative diseases ( Chik et al, 2013 ) such as AD ( Liu et al, 2014 ; Lin et al, 2016 ) and Parkinson’s disease (PD) ( Pan et al, 2015 ), and also the prevention of hypertension ( Zhang et al, 2016 ). Upon previously detected disease modules, a network illustration of potential interactions between herbs and AD, hypertension related gene targets was constructed to speculate the synergistic effect of herb formula ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…TMGTY consists of 11 Chinese herbs, such as Rhizoma Gastrodiae ( Tianma ), Ramulus Uncariae Cum Uncis ( Gouteng ), Concha Haliotidis ( Shijueming ), Fructus Gardeniae Jasminoidis ( Zhizi ), and Radix Scutellariae Baicalensis ( Huangqin ). TMGTY was prescribed to alleviate hypertension-related symptoms and also showed therapeutic effects against dementia and Alzheimer’s disease (AD) ( Liu et al, 2014 ; May et al, 2016 ; Zhang et al, 2016 ; Chen et al, 2017 ). TMGTY was one of the 10 most commonly used formulae for treating AD in Taiwan, according to a cohort study of one million patients ( Lin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Xuefuzhuyu decoction, a TCM used for coronary heart disease, is composed of 11 compounds. A study showed that Xuefuzhuyu decoction treatment could decrease cardiac fibrosis induced by hypertension and inhibit expression of TGF-β1 [49]. The bioactive components of Xuefuzhuyu that attenuate myocardial fibrosis by acting on TGF-β1 signaling pathways may include carthamin yellow, ferulic acid sodium, ligustrazine, amygdalin and paeoniflorin which are extracted from Carthamus tinctorius, Angelica sinensis, Ligusticum striatu, Prunus persica and Paeonia lactiflora Pall , respectively.…”
Section: The Mechanisms Of Tcm In Treating Hfmentioning
confidence: 99%